Chromosomal damage among medical staff occupationally exposed to volatile anesthetics, antineoplastic drugs, and formaldehyde - Musak, Ludovit; Smerhovsky, Zdenek; Halasova, Erika; Osina, Oto; Letkova, Lucia; Vodickova, Ludmila; Polakova, Veronika; Buchancova, Janka; Hemminki, Kari; Vodicka, Pavel (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVES ': 'Structural chromosomal aberrations in blood lymphocytes represent a biomarker for cellular damage caused by genotoxic carcinogens and are an indicator of increased cancer risk. We evaluated the association between frequencies of total chromosomal aberrations, chromatid- and chromosome-type aberrations, and occupational exposures to volatile anesthetics, antineoplastic agents, and formaldehyde among 601 medical professionals. ' ' METHODS ': 'Chromosomal damage among exposed individuals and unexposed controls was determined by conventional cytogenetic analysis. We used binary logistic regression to evaluate the effects of workplace exposures and major confounders on chromosomal damage. ' ' RESULTS ': 'Significantly higher frequencies of total chromosomal, chromatid-type and chromosome-type aberrations were observed among subjects occupationally exposed to volatile anesthetics, antineoplastic agents, and formaldehyde compared to age- and sex-matched controls (P<0.0001). The risk of an increased frequency of chromosomal aberrations was associated with exposure to anesthetics [odds ratio (OR) 3.9, 95% confidence interval (95% CI) 2.7–5.8], cytostatics (OR 2.7, 95% CI 1.9–3.9), and formaldehyde (OR 1.7, 95% CI 1.1–2.7). No other covariate contributed significantly to the model. Chromatid- and chromosome-type aberrations were associated with exposure to anesthetics and cytostatics without any contribution of other variables. Stratified data analysis showed the risk of increased chromosomal aberrations among non-smoking female nurses and physicians exposed to anesthetics, cytostatics and, partially, formaldehyde. Chromatid and chromosome exchanges were significantly higher in the exposed groups than among controls. ' ' CONCLUSION ': 'Our findings indicate that the presence of genotoxic compounds in operating rooms, oncological units, and pathological departments results in a significant increase of chromosomal damage (impair of chromosomal integrity) among medical workers employed in these facilities.
Keywords: anesthesiologist; antineoplastic drug; chromosomal aberration; chromosomal damage; formaldehyde; health risk; hospital staff; medical staff; occupational exposure; oncological department; pathological department; volatile anesthetic